INTERNALISASI NILAI KEBUDAYAAN SUNDA DALAM PROGRAM REBO NYUNDA DI KOTA BANDUNG - Choerunisa, Kulsum; Dahliyana, Asep (Universitas Pendidikan Indonesia, 2016)
The study was backed by the fears of loss of culture of sunda in West Java, especially in Bandung. This caused the modernization cannot be avoided by all layers of society, where technological progress is faster than the advancement of values and culture. In Bandung, there have been programs Rebo Nyunda held every Wednesday by the entire community of Bandung, especially students with language and dress of sunda. However, for the implementation of the programme of the community Rebo Nyunda yet entirely able to implement, especially for the young generation of students as the successor Nations. To get an overview about the internalization of cultural value in the program Nyunda Rebo, researchers using qualitative approach. The research States that students are still very influenced by modernization, there are some difficulties that students internalize the value of Sundanese culture, and some have a desire to develop a culture of sunda but the environment has not been supportive. Factors restricting the internalization of the values that is consciousness itself, because the students are still lack of knowledge, peers frequently make fun of, and environment outside of school.